Field measurement data - Aakala, Tuomas; Shimatani, Ichiro; Abe, Toshihiro; Kubota, Yasuhiro; Kuuluvainen, Timo (Dryad Digital Repository, 2015)
The file contains field measurements of trees, including site (1 to 48), coordinates (x,y,z, in meters), tree diameter and height, species, crown centroid location (x, y, in meters), and crown vector length (in meters) and direction (degrees).